Cooperation or Isolation? Muslim Congregations in a Scandinavian Welfare State: A Nationally Representative Survey from Sweden - Borell, Klas (Review of religious research, 2013)
In the Scandinavian welfare context, the emphasis on cooperation between public authorities and the nonprofit sector continues to be a central institutional characteristic. But to what extent have the new Muslim congregations adapted to the Scandinavian tradition of organizational cooperation, and what circumstances—internal or external to these organizations—promote or disrupt the development of such cooperation? This study is based on a nationwide survey of local Muslim congregations in Sweden (n = 105). No support was found for the widespread notion that European Muslim congregations tend to exist as separate enclaves. The powerful discursive emphasis on organizational cooperation in Scandinavia creates vital opportunity structures, but local variations in demographic and socioeconomic conditions also seem to have an impact. Among internal factors that influence willingness to cooperate is not least the degree of ethnic heterogeneity; openness to different Muslim traditions—a precondition for a multiethnic congregation—is seen to correspond to a greater openness to the wider society.